Entrepreneurial Education in Middle - Level Tertiary Colleges in the Rift Valley of Kenya - David E. Lawver; Matt Baker; Raphael Mwiti Gikunda; Juma Magogo; Michael Kanyi (Journal of International Agricultural and Extension Education, 2018)
This study adds to the knowledge base of Entrepreneurial Education (EE)in selected technical training institutes in Kenya.Using qualitative research inquiry, semi-structured interviews were conducted with aquestionguidebookand follow-up questioning. Data were collected from students, instructors,and administratorsselected through purposive sampling.Open and axial coding wasused to categorize the transcribed interview responses. Peer review was used to ensurecredibility and confirmability. The results reveals that the learning institutions prepared students as entrepreneurs through coursework, mandatory field internships, internal projects, participation inagricultural and business fairs, and providing startup capital for cooperative shops.EE delivery facesnumerous constraints including inadequate start-up capital, inadequate access to land, and output and input market resulting from poor infrastructure, competition, lack of marketing skills, and exam-oriented curricula.Dairy, horticulture, poultry, and apiculture enterprises were identified as the most promisingand viable enterprises for graduates of middle-level tertiary institutions. In conclusion, EE was being offeredin these institutions as certificate coursesor integratedas a topic in their existing curricula. In order to improve upon the delivery of the programs, the institutions needed to upgrade learning facilities, incorporating ICT in the curricula, enhancepractical learning, conduct rigorous follow-up evaluations of graduates, and establish business incubators for providing start-up capital to graduates
Keywords: Africa; entrepreneurship education; planning and evaluation; curriculum models